The effects of youtube video on the tourism destination image (Case study of tourism in Shogran, Pakistan) - Mohammad Alam; Muhammad Aqeel (Borneo Novelty Publishing, 2025)
Purpose – The purpose of the research is to analyze how YouTube travel vlogs impact tourist opinions, contentment, and decision-making, with a focus on Shogran, a popular tourist site in Pakistan.Methodology/Design/Approach– The research uses both primary and secondary data sources. It analyzes YouTube travel vlog content and conducts viewer polls to determine how online visual content impacts destination image and effects tourism-related behavior. The study also investigates the use of public relations methods in digital tourist promotion.Findings – According to the study, YouTube has a considerable impact on the destination image of Shogran, impacting tourists' opinions and travel decisions. It demonstrates how digital platforms, particularly YouTube, have outperformed traditional marketing tactics in tourism promotion, particularly in developing nations such as Pakistan.Originality/value – This study adds to the expanding set of information about digital tourism marketing by providing insights into the effectiveness of user-generated material, notably YouTube vlogs, in promoting lesser-known locations. It underlines the importance of strategic public relations tactics in digital content generation to increase tourism appeal and reach.